2006
DOI: 10.1590/s1413-35552006000400009
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade da freqüência cardíaca em diferentes faixas etárias

Abstract: Objetivo: O objetivo deste trabalho foi estudar a variabilidade da freqüência cardíaca (VFC) de 40 voluntários saudáveis, com diferentes faixas etárias, divididos em 4 grupos iguais, com as seguintes características: a) grupo 1 com idade entre 20 e 30 anos (média ± dp = 23±2,8 anos); b) grupo 2, entre 31 e 40 anos (34,7±2,1 anos); c) grupo 3, entre 41 e 50 anos (46,4±3,4 anos); d) grupo 4, entre 51 a 60 anos (54,9±2,0 anos). Método: foi utilizada como ferramenta de investigação a análise da VFC feita nos domín… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
30

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 22 publications
3
28
0
30
Order By: Relevance
“…Moreover, these indexes also allow verification of the influence of factors such as age [4,7,37,79,80], gender [81][82][83] and exercise [17][18][19]29,38] on the autonomic control. Table 2 shows studies using HRV in various physiological and pathological conditions.…”
Section: Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these indexes also allow verification of the influence of factors such as age [4,7,37,79,80], gender [81][82][83] and exercise [17][18][19]29,38] on the autonomic control. Table 2 shows studies using HRV in various physiological and pathological conditions.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Table 2 shows studies using HRV in various physiological and pathological conditions. Carnethon et al [56] Novais et al [29] Menezes et al [60] Terathongkum et al [61] Takahashi et al [55] Bittencourt et al [26] Pecyna [63] Carney et al [54] Limongelli et al [58] Karas et al [59] Larosa et al [62] Javorka et al [38] Catai et al [7] Weerapong et al [41] Mello et al [37] Paschoal et al [72] Sin DD et al [66] Kudaiberdieva et al [65] Lopes et al [71] Neves et al [73] Furuland et al [68] Lopes et al [79] and Paschoal et al [80] observed that the aging process causes a depletion of vagal tone and consequent increase in sympathetic activity, therefore older individuals have a lower HRV. In 2006, Rajendra Acharya et al [4] observed that HRV is lower with age and the variation is greater in women.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…This activation can be affected by the individual's breathing (Taelman et al, 2011). Hjortskov et al (2004) observed that mental stress during computer work leads to changes in HR and to a sustained increase in BP, and that these effects are reverted resting (Paschoal et. al., 2006).…”
Section: Methodsmentioning
confidence: 99%
“…The wide possibilities for using HRV added to the ease of data acquisition enables its use for the identification of ANS-related phenomena in individuals of different ages and states of health, as well as making evaluation possible in individuals during rest or exercise (1,(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%